Investigation on Spectroscopic, Thermal and Antimicrobial Activity of Newly Synthesized Binuclear Cr(III) Metal Ion Complex - Islam, M. R.; Shampa, J. A.; Kudrat-E-Zahan, M.; Haque, M. M.; Reza, Y (Journal of Scientific Research, 2016)
Binuclear Cr(III) metal ion complex was synthesized using diphenylacetic acid as primary ligand and 2-methyl pyridine (2-picoline) as secondary ligand. The synthesized complex was characterized by conductivity, FTIR, UV-Vis spectroscopy, magnetic moment and thermogravimetric analysis (TGA). FTIR spectra indicated the coordination of deprotonated diphenylacetic acid and 2-picoline through nitrogen and oxygen. The presence of water molecules inside the coordination sphere of the complex was confirmed from IR spectrum and TGA analysis. Binuclear and octahedral structure of the Cr(III) complex confirmed by TGA, UV-Vis spectroscopy and magnetic moment measurement. The complex showed moderate antibacterial activity with no antifungal activity.